The face of war: Trauma analysis of a mass grave from the Battle of Lützen (1632) - Nicklisch, Nicole; Ramsthaler, Frank; Meller, Harald; Friederich, Susanne; Alt, Kurt W. (PLOS ONE, 2017)
Contemporary accounts of battles are often incomplete or even erroneous because they reflect the—often biased—viewpoints of the authors. Battlefield archaeology faces the task of compiling an historical analysis of a battle and of gathering all the available facts. Besides cultural historical evidence and artefacts, the human remains of those who have fallen in battle also provide invaluable information. In studying mass graves from a military context, the injury types and patterns are significant. They allow us to reconstruct the circumstances surrounding the soldiers’ deaths and provide information on the hostilities that occurred on the battlefield. One such mass grave was discovered in 2011 at Lützen, Saxony-Anhalt (Germany). Based on its geographical location and on the results obtained from archaeological examinations carried out in the area, the grave could be dated to the Thirty Years War (1618–1648). Further archaeological research confirmed that the dead had been soldiers from the Battle of Lützen (1632). The mass grave was block-lifted and then comprehensively examined at the State Museum of Prehistory in Halle (Saale). As well as osteological examinations to determine age, sex, height, state of health, i.e. diseases or injuries, imaging methods were also employed and histological and isotopic analyses carried out. The focus of this study was on the injuries sustained by the soldiers both prior to and during the battle. The results revealed that the 47 deceased had been between the ages of 15 and 50 when they died. Numerous healed injuries showed that the men had often been involved in violent encounters. Approximately three in every four soldiers had injuries that could have been fatal. Wounds inflicted by handguns, particularly to the skull, were predominant. The integrative analysis of the archaeological and anthropological data allowed us to conclude that the majority had been killed during a cavalry attack.